Iatrogenic Pneumoperitoneum Following Peritoneal Dialysis in A Neonate with Methylmalonic Acidemia: A Rare Case Report - Muhammad Bin Hammad; Fatima Tariq Butt; Adnan Mirza; Ibrahim Mirza (Pakistan Journal of Medicine and Dentistry)
This is a case of a neonate who was brought to the hospital at 46 hours of life with symptoms of fatigue, difficulty breathing and hypoglycemia for the past 6 hours. His septic workup was normal; however, labs were consistent with high anion gap metabolic acidosis, hyperammonemia, and urine positive for methylmalonic acid. Due to persistent encephalopathy and high ammonia levels, he was intubated, and peritoneal dialysis (PD) was started. On day 3 of PD drain placement, the baby developed abdominal distension. Abdominal x-ray showed a football sign indicative of pneumoperitoneum. Tube feeding was started with special formula milk. The neonate improved clinically and was discharged at the 11th day of life.